ART EXPERIMENT OF THE "BURIME" ART GROUP: FROM UTOPIA TO PRACTICE - Naydenko, Viktoriia (International Journal of Innovative Technologies in Social Science, 2022)
The article examines the activity of the modern Ukrainian art group "Burime" in the context of their artistic experiments. The group emerged in Kharkiv at the end of the 1990s, during the turning point for the Ukrainian authorities, and has been an active participant in the art scene of Ukraine for more than 30 years. The members of the Burime’s art association embodied the utopian idea of Vincent van Gogh with their collective writing, who believed that the highest art could be created only by the joint efforts of artists. Burimists stand out from other art groups with their original visual language and specific approach to painting. They create joint large-format monumental works in which vital themes are revealed. In addition, the article outlines the connection between design and painting, which was successfully combined in the works of the members of the Burime art group and is part of their technical experiments. The events that shaped their design and imaginative thinking are also highlighted. The obtained results of the research will be applied in the scientific work, which is devoted to experimental searches in the painting of modern Kharkiv artists.